Sravnitel'nyj analiz rezul'tatov sbornych ženskich komand Rossii i SŠA na 49-m cempionate mira po sportivnoj gimnastike 2019 goda v Štutgarte (Germanija) - Somkin, A. A. (Uchenye zapiski universiteta imeni P.F. Lesgafta, 2019)
The 49th FIG Artistic Gymnastics World Championships 2019 in Stuttgart (Germany) were the second stage of the Olympic National teams and individual female gymnast`s qualification for the XXXII Olympic Games (2020) in Tokyo (Japan). The article provides the comparative analysis of the Russian and the USA National women`s teams results at the qualification competitions, team final, individual all-around and apparatus finals. The special attention in the publication is paid to the best results of the Russian National team and its leader Angelina Melnikova at these last world championships before Olympic Games.